Inconstitucionalidad de algunas normas sobre materia conciliable por violar el derecho de acceso a la Administración de Justicia y la autonomía privada (2014)
This article poses general aspects on the right of Access to justice administration and the relation exiting between such a right and the extra-judicial conciliation in law as another mechanism to Access to the same. In this connection effort, we pose how it can be real or effective for the citizen, the right to access through the conciliation instrument, in contrast with some conciliation norms which close the opportunity that parties comply with the philosophy which orients both theconciliating figure and the effective access to justice administration and private autonomy, to finally conclude that such norms are illegal, because they violate several norms of 1991 Colombian Political Constitution.